Early years assessment : communication and language - Fitzhenry, Trudi; Murphy, Karen (London : Featherstone, 2017)
With the revision of the EYFS, Communication and Language became one of the three Prime Areas of learning. This book seeks to provide valuable guidance for practitioners across the entire Early Years provision. This is a practical tool that will enable practitioners to be innovative and exciting whilst meeting their targets. It includes suggestions for parents to try out at home, and a variety of ideas to inspire adult-led learning.
Keywords: Early childhood education; Communication -- Study and teaching (Early childhood).; English language -- Study and teaching (Early childhood).